Eksplorasi Pengalaman Siswa SMK dalam Mengembangkan Citra Diri melalui Program Pelatihan Beauty Class - Nonik Silvi Aprilia Berliyanti; Achmad Imam; Sri Dwiyanti (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
Professional training is crucial for enhancing the work readiness of vocational high school (SMK) students; however, the frequent gap between theoretical knowledge and practical application often leads to a poor first impression and challenges in adapting to the workplace. To address this issue, this study explores the experiences of 10th and 11th-grade students in the Hospitality, Culinary Arts, Office Management, and Accounting programs at SMK Barunawati in Surabaya as they build a positive self-image through the beautyclass training program. Using a qualitative methodology, research data was collected through participant observation and in-depth interviews with participating students. The findings indicate that this practical “learning by doing” intervention provides significant practical benefits, successfully transforming theoretical grooming knowledge into real-world grooming skills. Specifically, students mastered industry-standard techniques such as proper skin preparation, foundation selection based on skin undertones, and natural eyebrow shaping. In conclusion, mastering these grooming skills effectively reduces self-doubt and builds a strong foundation of self-confidence, making the beauty class program a crucial catalyst in holistically shaping students’ professional image for their Field Work Practice (PKL) and future job readiness.